Coeliccia southwelli sp. nov. (Odonata: Zygoptera: Platycnemididae) from Mount Dulit, Sarawak - Dow, Rory A.; Reels, Graham T. (Zootaxa, 2011)
Coeliccia southwelli sp. nov. is described from Mount Dulit, Miri and Kapit Divisions, Sarawak, Malaysian Borneo. It belongs to the borneensis-group of species, and is the sixth species from this group to be described from Borneo. New material of other borneensis-group species is put on record.